The Journal Of Muamalat and Islamic Finance Research : Harmonizing Shari'ah Rulings in Islamic Finance : Strategies and Challenges - Amir Shaharuddin (UNIVERSITI SAINS ISLAM MALAYSIA (USIM), 2015)
The main objective of this paper is to discuss the ways and challenges in harmonizing shari'ah rulings in islamic finance industry. This paper will be valuable addition to the existing literature in the effort towards enhancing the governance of shari'ah matters in Islamic finance industry.